2016
DOI: 10.2118/183637-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Thermal-Hydraulic-Mechanical Simulation With Application of Thermal Recovery in Fractured Shale-Gas Reservoirs

Abstract: Shale gas is playing an important role in transforming global energy markets with increasing demands for cleaner energy in the future. One major difference in shale gas reservoirs is that a considerable amount of gas is adsorbed. Up to 85% of the total gas within shale may be found adsorbed on clay and kerogen. How much of the adsorbed gas can be produced has a significant impact on ultimate recovery. Even with improving fracturing and horizontal well technologies, average gas recovery factors in U.S. shale pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…It is noted that the heat capacity of rock is at least 100 times larger than that of gas, and the formation porosity is normally small in shale reservoirs. Therefore, C eq and κ eq are dominated by the properties of formation rock [22]. K g and α g are the gas bulk modulus and the gas thermal expansion coefficient, respectively.…”
Section: Energy Conservation Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noted that the heat capacity of rock is at least 100 times larger than that of gas, and the formation porosity is normally small in shale reservoirs. Therefore, C eq and κ eq are dominated by the properties of formation rock [22]. K g and α g are the gas bulk modulus and the gas thermal expansion coefficient, respectively.…”
Section: Energy Conservation Equationmentioning
confidence: 99%
“…Some studies [20,21] estimate that the adsorbed gas shares are 20% to 85% of the total gas content. Therefore, enhancing gas desorption will inevitably increase shale gas recovery [9,10,22,23]. Existing experimental studies reported the effect of temperature on shale gas adsorption [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal stimulation can account for about 60% of oil production in our world today (Chekhonin et al, 2012).Though several studies have been conducted on how to improve heavy oil/shale oil recovery by elevating the formation temperature, very few have considered the implementation of similar thermal techniques as a way of enhancing gas recoveries (Yue et al, 2015). Wang (2016) demonstrated the efficiency of thermal stimulation largely depended on the gas adsorption and rock properties of the formation. Thus by altering the gas adsorption/desorption behaviour through thermal stimulation, more gas could be recovered from hydraulically fractured shale gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%